A Study on Customer Perceived Value on Purchase Intention of Personal Care Products in Malaysia: Special Reference to Green Personal Care Products. - Fu, Qian (2014)
From the customers’ perspective, ‘customer perceived value’ is another fundamental source to affect the demand of products or service apart from the conventional physical, psychological and social advantages. Also more marketing researchers are focusing on developing this ‘perceived value’ to promote the continuous development in marketing. This study focuses on personal care products like soap, shampoo, lotion and makeup, which is becoming the second major consumption product in Malaysia. However, few research have been carried out green personal care products in developing economies; which can help expand the green marketing concept in a country. With government support in enhancing green purchasing and expanding the environmental awareness demand for green personal care products is very significant in Malaysia. With the green personal care product consumption as the objective this study, it is to explore the impact of customer perceived value on purchase intention. The independent variables being focused are: Functional value, Emotional value, Social value, epistemic value and Conditional value. This study, will also look at the influence demographic factors have towards purchasing intention for green personal care products. In order to complete this research, this study target 350 respondents with questionnaires to gather the data for Malaysia. This study is completed into the first chapter, will be introduction on this research, which will include the background, problem statement, objectives and the significance of this research. Limitations and scope on this research are mentioned in this chapter as well. Chapter two will be literature review, which will deal with the perceived value theory and purchase intention. In chapter three will be the framework and hypothesis to define the dimensions of perceived value that influence purchasing intention on green personal care products. While chapter four is the analysis on data gathered. All data will be used for the SPSS analysis. Finally, chapter five will be the conclusion and recommendations.